2013
DOI: 10.1021/jp407539c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of RuO2/TiO2Mesoporous Heterostructures and Rationalization of Their Enhanced Photocatalytic Properties by Band Alignment Investigations

Abstract: Nanoporous RuO 2 /TiO 2 heterostructures, in which ruthenium oxide acts as a quasi-metallic contact material enhancing charge separation under illumination, were prepared by impregnation of anatase TiO 2 nanoparticles in a ruthenium-(III) acetylacetonate solution followed by thermal annealing at 400 °C. Regardless of the RuO 2 amount (0.5−5 wt %), the asprepared nanocatalyst was made of a mesoporous network of aggregated 18 nm anatase TiO 2 nanocrystallites modified with RuO 2 according to N 2 sorption, TEM, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
140
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 74 publications
12
140
1
Order By: Relevance
“…Recently Prouzet's [59] group has shown that the indirect bandgap model gives better agreement on the E g values of anatase nanoparticles. Further, Uddin et al's [60] report on the bandgap of TiO 2 show that the indirect bandgap model gives lower E g , close to the reported bulk values (3.2 eV), than the estimates obtained using direct bandgap model. We calculated both direct and indirect bandgap values as obtained from (Fhν) 2 vs. hν and (Fhν) 1/2 vs. hν plots, respectively, where 'F' is the Kubelka-Munk (K-M) function, 'h' is Planck constant and 'ν' is the frequency of the photon (Figs.…”
Section: Resultssupporting
confidence: 56%
“…Recently Prouzet's [59] group has shown that the indirect bandgap model gives better agreement on the E g values of anatase nanoparticles. Further, Uddin et al's [60] report on the bandgap of TiO 2 show that the indirect bandgap model gives lower E g , close to the reported bulk values (3.2 eV), than the estimates obtained using direct bandgap model. We calculated both direct and indirect bandgap values as obtained from (Fhν) 2 vs. hν and (Fhν) 1/2 vs. hν plots, respectively, where 'F' is the Kubelka-Munk (K-M) function, 'h' is Planck constant and 'ν' is the frequency of the photon (Figs.…”
Section: Resultssupporting
confidence: 56%
“…19 However, different conclusions have been reported by several groups, where 1 ~ 5 wt% of RuO2 has been suggested to provide the best performance. 21,35 It can be concluded that optimizing the spatial distribution of RuO2 loading on rutile TiO2 support strongly depends on the synthesis method, support nature and experimental conditions. It is critical to develop a synthesis method that allows the isolation of small amounts of RuO2 on TiO2.…”
Section: Resultsmentioning
confidence: 99%
“…The broad and weak spectrum in the inset indicates the formation of mixtures of Ru 0 and oxidized Ru n+ species (n = 2 ~ 4). 8,10,11,16,21,35 Due to the intrinsic submetallic property of RuO2, [8][9][10][11]21,31,[33][34][35] these highly dispersed ruthenium species behave as quasi metallic contact materials to enhance both the conductivity and transfer of photoinduced holes from TiO2 valence band, further facilitating the charge separation, so that the electrons freely migrate from the conduction band of TiO2, reducing the protons and/or water to generate gaseous H2. The local geometry of the prepared materials was further studied by electron microscopy.…”
Section: Structure-photoactivity Correlation Over Ruo2/tio2 Heterostrmentioning
confidence: 99%
See 2 more Smart Citations